Kinerja Lingkungan dan Kinerja Keuangan - Meizi Tri Andani1; Sindy Monica; Sefti Fitriyani; Vinda Fristiani; Karima Mufidah (Journal of Student Research, 2025)
This research aims to synthesize the results of previous research regarding Environmental Performance and Financial Performance through a Systematic Literature Review (SLR). This research uses SLR to present qualitative data to determine developments in Environmental Performance and Financial Performance issues. There are several parameters used, namely journal sources, variable and theory mapping as well as fields of science, research approaches and companies. The results of this research show that there are 30 articles originating from accredited and national journals during the 2020-2024 period. Financial performance topics are linked to environmental performance, company value, stakeholder theory is the most widely used theory and the dominant use of qualitative methods in research on environmental performance and financial performance. Manufacturing companies are companies that research a lot of environmental performance and financial performance issues.